Stabilization Policies in Interdependent Economies: Proceedings of the Conference held at the University of Paris-Dauphine, March 25-27, 1971. - Claassen, Emil Maria; Salin, Pascal (Amsterdam : North-Holland Pub. Co., 1972)
The book contained highlights of conference proceedings that explained the appropriate combination of monetary, fiscal, exchange rate and other conceivable stabilization policies; with the formulation of stabilization policies in a world of limited information; with policy for prescriptions in open economies according to the Keynesian and monetarist view.
Sole distributor for the USA: American Elsevier, New York.
Proceedings of the 1st of a series of meetings; proceedings of the 3rd are entered under Paris-Dauphine Conference on Money and Monetary Problems.
Includes bibliographies.
rua 16/06/17
Loans.
Keywords: Monetary policy; Fiscal policy